Adaptive Hybrid Mixed Finite Element Discretization of Instationary Variably Saturated Flow in Porous Media - Knabner, Peter; Schneid, Eckhard (High Performance Scientific And Engineering Computing, 2002)
For the Richards equation, a nonlinear elliptic-parabolic partial differential equation modelling saturated-unsaturated flow in porous media, we present a hybrid mixed finite element discretization. The efficiency of the algorithm is improved by local time step and grid adaption. The adaption algorithms are based on rigorous error estimators, whose derivation is indicated. Examples elucidate the performance of the algorit